[tex]a)~~2 \sqrt{2} \times (-3) \sqrt{2} + 15 = \\
= -2 \times 3 \times \sqrt{2} \times \sqrt{2} + 15 = -6 \times 2+ 15 = -12+15=\boxed{3} \\ \\
b)~~ \frac{6 \sqrt{12}}{2\sqrt{3}} - 7 = \frac{6 \sqrt{4 \times 3}}{2\sqrt{3}} - 7 =
\frac{6 \times 2\sqrt{3}}{2\sqrt{3}} - 7 = 6 - 7 = \boxed{-1} [/tex]
[tex] c)~~\frac{ \sqrt{98}-\sqrt{50} }{-\sqrt{2}} = \frac{ \sqrt{49 \times 2}-\sqrt{25 \times 2} }{-\sqrt{2}} = \frac{ 7\sqrt{2}-5\sqrt{2} }{-\sqrt{2}} = -\frac{ 2\sqrt{2}}{\sqrt{2}} = \boxed{-2} [/tex]